PENGEMBANGAN MEDIA DIORAMA BERBASIS AR MATERI PEMBELAJARAN IPAS KELAS V UPTD SDN 1 KUNYIT - Rully Wahyu hidayati; Qoriati Mushafanah; Henry Januar saputra (STKIP Subang, 2025)
This research is based on the low utilization of varied learning media in class V UPTD SD Negeri 1 Kunyit. Teachers still dominate using conventional media such as whiteboards, package books, and worksheets, so that learning is less interesting and has minimal visual stimulus. This condition makes it difficult for teachers to deliver abstract science subjects, especially material about changes in the earth due to natural events. In addition, the researcher's experience during the teaching campus program showed that students responded very positively to the use of visual and interactive digital media, characterized by their increased enthusiasm and participation. The objectives of this research and development are: to describe the media development process, to determine the validity and practicality of media, and to find out the response of students to AR-based diorama media in the science learning material of class V UPTD SD Negeri 1 Kunyit. This type of research is Research and Development (R&D) that develops AR-based Diorama Media. The development process uses the ADDIE (analysis, Design, Development, Implementation, and Evaluation) model. The field trial was carried out involving 13 students of class V UPTD SD Negeri 1 Kunyit. Data collection was carried out through interviews, observations, and questionnaires to assess the feasibility and user response to the media. The results of the study show that Augmented Reality (AR)-based diorama media is stated to be very feasible to use, based on the assessment of media experts with an average of 96.25% and material experts with an average of 96.25%. The practicality of the media was also stated to be very practical, as evidenced by the results of 100% teacher responses and 98.46% student responses. Thus, it can be concluded that AR-based diorama media is valid and very practical to be used as a science learning media for grade V in elementary schools.